The impact of COVID-19 on morbidity and mortality in neck of femur fracture patients: A prospective case-control cohort study. (November 2020) - Ward, A. E.; Tadross, D.; Wells, F.; Majkowski, L.; Naveed, U.; Jeyapalan, R.; Partridge, D. G.; Madan, S.; Blundell, C. M.
No abstract available